The Evaluative Language of HIV/AIDS Campaigns Texts: A Case Study in Japanese Ministry of Health, Labor, and Welfare - M Ikhwan F Nurjaman; Eva Tuckyta Sari Sujatna; Inu Isnaeni Sidiq (Universitas Negeri Semarang, 2026)
This study examines the evaluation language of HIV/AIDS campaign texts published on the official website of Japan’s Ministry of Health, Labour and Welfare. Drawing on Martin and White’s appraisal framework, it analyzes how attitude, engagement, and graduation are deployed to construct public understandings of HIV/AIDS. Using a qualitative case study design, the study examines campaign materials collected from January to March 2025 through purposive sampling and document-based analysis. The findings show that the texts rely on a dual evaluative strategy. On the one hand, affect is dominated by insecurity, dissatisfaction, and unhappiness, foregrounding fear, stigma, uncertainty, and the continuing social burden of HIV/AIDS. On the other hand, positive evaluations are also salient, particularly in references to medical progress, early detection, treatment access, and institutional support. In the judgement system. The text endorses responsible, informed, and preventive behaviour while condemning ngegligence, discrimination, and stigmatizing practices. In appreciation, positive valuation is attached mainly to advances in treatment and public health services, although systemic limitations and persistent prejudice are also critically represented. Overall, the discourse frames HIV/AIDS simultaneously as a medical, social, and moral issue. The study contributes to appraisal-based discourse analysis and offers insights for more inclusive and effective health communication.